Analysis of Workload In Fishermen’s Wives On Gender Perspective In Sungai Piring Village, Batang Tuaka Subdistrict, Indragiri Hilir Regency - Mutiara Cendrakasih; Kusai '; Firman Nugroho (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
The Study was conducted in February 2017 in Sungai Piring village, Batang Tuaka subdistrict, Indragiri Hilir regency. This study aims to determine the workiload of women in the fishermen’s family from perspective gender point of view. This study using participatory actiob research (PAR) method. The objects of this study were the fishermen’s wives and the respondents were 20 wives with 3 informan. The research used purposive sampling and the methods of data collection was using observation, interview and documentation. The analysis technique that is used is descriptive analysis. The result shows that the workload of the fishermen’s wives are more difficult than their husband, it is proved by the working schedule fishermen wife which more intense than husband.Keyword: gender, workload, participatory action research (PAR)